Differential evolution in shortest path problems - Guerreiro, Pedro (2018)
This paper proves that the Diﬀerential Evolution (DE) algorithm is valid to solve the Shortest Path (SP) problem in random, median sized networks. From the trials, we have obtained an 9% accuracy, in the worst case scenario.